تقارب النقاط السرجية لدوال محدبة – مقعرة بالنسبة إلى مسافة - هاوسدورف (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2018)
الهدف من هذا البحث هو دراسة وتعميم بعض النتائج المتعلقة بـ - الحلول لمسائل بمتحول واحد (محدبة) إلى - الحلول لمسائل بمتحولين ( محدبة-مقعرة). إذ نعرف مسافة - هاوسدورف على صفوف الدوال المحدبة-المقعرة كما نعرف مسافة - هاوسدورف على صفوف دوال ليست بالضرورة محدبة-مقعرة. ومن أجل المتتالية  ندرس تقارب هذه المتتالية بدلالة تقارب المقاطع الموافقة لها،  ثم نبرهن أن متقاربة نحو بالنسبة إلى مسافة - هاوسدورف إذا وفقط إذا كانت متتالية المجموعات  متقاربة نحو المجموعة   بالنسبة إلى مسافة - هاوسدورف . ونحصل على نتائج مشابهة تتعلق - التفاضلات الجزئية  لدوال محدبة-مقعرة ومغلقة معرفة على فضاءات باناخ .   التصنيف الرياضي لهذا الموضوع AMS        الأول :  46B20       الثاني  :   49J45     .   The aim of this paper is to study and generalize some results concerned with the - solutions of one variable (convex) problems to the - solutions bivriables (convex-concave) problems. We define the - Housdorff distanceon the classes to convex-concave functions and the - Housdorff  distance on the classes not necessary convex-concave functions. For the sequence ; We study the convergence of this sequence in terms of level sets convergence, and we show that the sequence is - Housdorff distance to  if and only if for each the sequence of sets  is - Housdorff distance convergent to . An analogous result holds for - Subdifferential of convex-concave closed functions defined on a Banach space.     AMS  Subject Numbers :   Primary :     46B20 Secondary :  49J45.